Effect of different organic loading rate on biological pretreatment to chemical pulping process - Ku Marsilla, Ku Ishak (2006)
Pulping is the process by which the fibres in the wood or non wood are separated and treated to produce pulp. Commercial non wood pulp production has been estimated to be 6.5% of the global pulp production and is expected to increase. One of the materials found to be promising was banana stem waste, which is very good source of cellulose. These approaches offer several advantages, since these raw materials can be produced annually and have generally lower lignin contents and lower than wood-based materials. A lignin content in banana stem waste is about 12.25%. The effect of different organic loading rate on biological pretreatment to chemical pulping process was initiated in this studies using mix culture that was obtained in banana plantation. The samples that have been treated appeared to give lower lignin contents than untreated. The cellulose composition for treated samples could be say as maintained although there are a very slight depreciation because of the degradation of cellulose give higher content of glucose. The organic loading rate used in this study are 2,5 and 8g/liter day.Organic loading rate of 5g/liter day are the most efficient and have the maximum production rate by the mix culture while the others are not so encouraging. This may have been caused by the limitation of one of the parameter that is the substrate. Theoretically, biological pretreatment is effective, more beneficial and have high interest in the industry due its potential to save energy, reduce chemical needs and have less impact on environment